The Impact Facilities and Promotion on Purchase Decision at Hotel Forte Balibo, Timor-Leste - Guterres, Alexandre de Sousa; Goncalves, Manuel; Soares, Elsa Da Costa; Sikki, Nurhaeni (Sinergi International Journal of Management and Business, 2024)
The objective of this research was to test and analyses the Facility influence the Purchase Decision at Hotel Forte Balibo, and to test and analyses the Promotional Analysis influence the Purchase Decision at Hotel Forte Balibo. The method used in conducting this research is a quantitative descriptive method. Hypothesis Results Test T (H1) Facility (X1) for Purchase Decision (Y), from the SPSS output results shows that the T-count value of the independent variable Facility (X1) with a level of 2,992 > and the Table value with a level of 1.676 or T-count > Table with an error rate of 0.05 or 5% With a level of confidence 95%. Meanwhile, the T-test hypothesis (H2) of the Promotion (X2) of the Purchase Decision (Y), from the SPSS output results, shows that the value T-count of the independent variable Promotion (X2) with a level of Facilities have a positive and significant influence on purchase decisions. The meaning of good facilities will increase Purchase Decision. The meaning of Consumers is to see A facility that generates indicators such as Special Plan, wrong design, Equipment, Illumination, Color and message that is transmitted in graphs will motivate and increase the Purchase Decision at Hotel Forte Balibo. Promotion has a positive and significant influence on Purchase Decision. This means that the Promotion that; good will increase the Purchase Decision. Means that consumers provide a Promotion value derived from the indicator.